THE INFLUENCE OF COMMERCIAL RANSUM PLUS OYSTER SHELL AS A CALCIUM SOURCE ON PRODUCTION OF CHICKEN EGGS OF ISA BROWN AGE 95 WEEKS - I. N. S., Rusnadi; Dewi, G. A. M. K.; Umiarti, A. T. (Jurnal Peternakan Tropika, 2020)
This study aims to increase the production of 95-week-old Isa Brown chicken eggs fed commercial rations plus oyster shell as a calcium. The study was conducted in Pesedahan Village, Manggis District, Karangasem Regency for 4 weeks. The research material used was Isa Brown laying hens aged 95 weeks. The research design used was a Completely Randomized Design (CRD) consisting of 4 treatments, namely commercial ration without the addition of calcium oyster shell as a control (A), commercial ration plus 1% oyster shell (B), commercial ration plus 2% clam oyster shell ( C), and commercial ration plus 3% of oyster shell (D), each treatment was repeated in 5 replications each repetition consisting of 5 chickens. The observed variables were ration consumption, daily egg production (hend day production), egg weight, and FCR. The results obtained after the administration of commercial ration treatment added 1%, 2%, and 3% of oyster shell can increase the weight of eggs that obtain an average of each of 0.44%, 0.49%, 0.78% significantly higher statistically significantly different (P <0.05) compared to treatment A, while all treatments did not statistically affect the ration consumption variable, daily egg production (hand day production), and FCR. Based on the results of this study it can be concluded that the provision of commercial rations with the addition of 2%, and 3% shells flour can increase egg weight but do not give the expected results on daily egg production (hen day production), ration consumption and FCR of aged Isa Brown chickens 95 weeks. Keywords : seashell flour, Isa Brown, egg production, commercial ration